Opini Audit Going Concern : Pengaruh Kualitas Audit, Audit Tenure, Kompleksitas Operasi, Likuiditas, Disclosure, dan Leverage pada Perusahaan yang Terdaftar di Indonesia Tahun 2020-2022: Going Concern Audit Opinion: The Effect of Audit Quality, Audit Tenure, Operating Complexity, Liquidity, Disclosure, and Leverage on Companies Listed in Indonesia in 2020-2022. - Sigolgi, Hudiya Aziza; Djamil, Nasrullah (MUI Kota Pekanbaru, 2024)
The objective of this study is to analyze the impact of Audit Quality, Audit Tenure, Operating Complexity, Liquidity, Disclosure, and Leverage on Going Concern Audit Opinions on the Indonesia Stock Exchange from 2020 to 2023. A sample of 39 observations from 13 manufacturing companies was selected using purposive sampling method. Logistic regression analysis was conducted to analyze the data, with support from SPSS 25 software. The study found that Audit Quality, Audit Tenure, Operating Complexity, Disclosure, and Leverage significantly influence Going Concern Audit Opinions in Manufacturing companies on the Indonesia Stock Exchange. However, the Liquidity variable did not show a significant effect. The study shows that the independent variables examined can account for 73% of the variation in Going Concern Audit Opinions, as indicated by a Nagelkerke R Square value of 0.730 or 73%. The remaining 27% is explained by factors outside of this research model. These findings offer valuable insights for stakeholders, such as regulators, auditors, and investors, about the factors that affect Going Concern Audit Opinions, particularly in the Manufacturing sector of the Indonesia Stock Exchange. This study recommends paying attention to aspects of Audit Quality, Audit Tenure, Operating Complexity, Disclosure, and Leverage in the audit process to anticipate and respond to potential problems with the sustainability of company operations. The language has been made more objective and formal, and the unnecessary phrase 'This study also suggests' has been removed. Additionally, the translation source has been mentioned to ensure transparency.